Eksplorasi dan Visualisasi Morfologis Jenis Moluska (Gastropoda dan Bivalvia) di Sungai Batang Merangin - Rivo Yulse Viza (BIOCOLONY, 2018)
The research about exploration and morphological visualization of freshwater Molusca (Gastropod and Bivalvia) in Batang Merangin river had been done. The research aims to observe the species of freshwater Gastropod and Bivalvia in Batang Merangin river and characteristic of each species. The method that have been used in this research was quadrant method. Three quadrants sized 1 x 1 m were settled at each station, and all Molusca spesimens that found inside the quadrants were collected and put on labeled container. The Molusca that captured was collected, cleaned, identified and characterized. Result of research showed that 3 species of Gastropod and 2 species of Bivalvia were found. Those are Terebia granifera, Melanoides tuberculata, Thiara sp, Rectidens sumatrensis and Pilsbryoconcha exillis.